2010
DOI: 10.1007/s11940-009-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Carotid Cavernous Fistulas

Abstract: The treatment of a carotid cavernous fistula (CCF) depends on the severity of the clinical symptoms, its angiographic characteristics, and the risk it presents for intracranial hemorrhage. In most instances, endovascular treatment is preferred.High-flow direct CCFs usually are traumatic or are caused by rupture of a cavernous aneurysm into the sinus, but a small percentage can be spontaneous. They usually present with sudden development of a clinical triad: exophthalmos, bruit, and conjunctival chemosis. All d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 35 publications
0
90
0
6
Order By: Relevance
“…5,17,42,52,88 This is demonstrated both clinically by reversal of the signs and symptoms of the CCF and angiographically by fistula obliteration with reversal of retrograde cortical venous flow and vascular steal. In a series of more than 200 patients presenting with posttraumatic direct CCFs, Higashida et al 26 reported complete fistula occlusion with preservation of the ICA in 88% of patients.…”
Section: 48mentioning
confidence: 99%
See 3 more Smart Citations
“…5,17,42,52,88 This is demonstrated both clinically by reversal of the signs and symptoms of the CCF and angiographically by fistula obliteration with reversal of retrograde cortical venous flow and vascular steal. In a series of more than 200 patients presenting with posttraumatic direct CCFs, Higashida et al 26 reported complete fistula occlusion with preservation of the ICA in 88% of patients.…”
Section: 48mentioning
confidence: 99%
“…10, 17,18,62 When conservative management is used, it is important to have close ophthalmological follow-up, with serial vision tests, intraocular pressure measurements, and funduscopic examinations. 49 Progressive visual decline, papilledema, and refractory elevation of intraocular pressure are all indications for emergency endovascular intervention.…”
Section: Conservative Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The usual clinical presentation of a direct high-flow CCF appears as a consequence of high-pressure arterial blood transmitted directly into the cavernous sinus and ophthalmic veins, leading to venous hypertension [7], which can include a various presentations such as proptosis, chemosis, conjunctival injection, cranial nerve pareses, and visual deficits, bleeding (from mouth, nose, or ears), and cerebral complications (intracranial hemorrhage, increased intracranial pressure, and steal phenomena) [8].…”
Section: Discussionmentioning
confidence: 99%